PERENCANAAN STRUKTUR GEDUNG “SUNTER PARK VIEW APARTMENT” SUNTER -JAKARTA UTARA - Widi Krismahardi; Pupuk Wahyuono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
The system structure is a combination of various structural elements are arranged in such a way as to form a whole structure that can bear loads planned, (Steffie Tumilar). Dual structural system is a combination of frame and shearwall, the system is very important to apply to high-rise buildings such as sunter Park View Apartment , North Jakarta, Indonesia given the location of the region are located in earthquake prone areas because three regional meetings tectonic indo-australian plate, the eurasian plate and the pacific plate clashing.